A modelling study of the role of marine protected areas in metapopulation genetic connectivity in Delaware Bay oysters. Issue 5 (20th September 2013) - Munroe, Daphne M.; Klinck, John M.; Hofmann, Eileen E.; Powell, Eric N.
ABSTRACT Management decisions concerning location and extent of marine protected areas (MPAs) both for exploited and unexploited resources rely on understanding how populations are interconnected. The potential effects of MPA location and external fishing pressure on genetic connectivity of eastern oyster (Crassostrea virginica) populations in Delaware Bay were examined. An individual‐based metapopulation model that includes post‐settlement population dynamics, larval dispersal, and genetic structure was used to simulate four oyster populations for two periods (1970s and 2000s) with distinct population and environmental conditions. Sensitivity analysis examined the influence of larval dispersal, and simulations included combinations of MPA location (which population was protected) and three fishing mortality rates for non‐MPA populations: low (4%), medium (8%) and high (30%); no fishing was allowed in the MPAs. Results showed (i) salinity‐driven changes in larval dispersal led to relatively small, population‐specific connectivity changes, (ii) MPAs can enhance the frequency of genotypes originating within protected populations in unprotected populations when fishing rates are high (30%), and (iii) demographic shifts can impose temporal variability on the influence of MPAs on connectivity. These results suggest that genetic consequences of siting MPAs must be considered in terms of present population and environmental conditions, as well as allowing for changes in population and genetic connectivity that may shift fundamentally over time. Simulation results indicate that siting protected areas for oyster restoration in low salinity (<12ppt) regions may interact with development of disease resistance in the metapopulation by altering genotype transfer from protected to unprotected downestuary populations. Copyright © 2013 John Wiley & Sons, Ltd.